La Fonction Maternelle et la Construction du Narcissisme Primaire - Boucherit, Saci (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2023)
The maternal function has several dimensions, involving in particular what will refer the child to his filiation and his sexual identity. Its exercise concerns in particular what will promote in the latter a progressive physical and psychic autonomy, from first aid to entry into adulthood. This is why reflections in this area do not only aim at the well-being of the mother; it also has consequences on the child, his subjectivity, his possibilities of growing up. Precisely, on the narcissistic level, the ability and also the difficulty of being a mother concern the fact of being able to consider one's child as a subject in its own right, separate from oneself. Very early on, a dialectic begins between the representations of the real child who arises and those of the expected ideal child. Our purpose will first be to try to show how this dynamic works and under what conditions it can either slow down or contribute to the necessary processes of detachment.
Keywords: القيم الذاتية -- ظاهرة الأمومة -- الاستقلالية الجسدية -- النرجسية الأولية